Tokenisme Perempuan dalam Politik Elektoral: (Studi Representasi Perempuan di DPRD Kota Cilegon) (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Women’s representation in legislative institutions is an important indicator for assessing the quality of democracy and gender equality in a political system. Indonesia has implemented an affirmative policy requiring a minimum quota of 30% female candidates in legislative elections. However, its implementation at the local level still faces various challenges. This study aims to analyze the phenomenon of tokenism and the forms of women’s political representation in the nomination and election process of members of the Cilegon City Regional House of Representatives (DPRD) for the 2024–2029 period. This research employs a qualitative method with a descriptive approach using literature review and secondary data analysis. The analysis is based on Hanna Pitkin’s theory of political representation, which categorizes representation into four types: formal, symbolic, descriptive, and substantive. The findings show that only 4 out of 40 seats in the Cilegon City DPRD are occupied by women, representing approximately 10% of the total membership, and this figure has remained unchanged compared to the previous period. This condition indicates a gap between the fulfillment of the female candidate quota at the nomination stage and the low level of electoral success. Furthermore, the political recruitment process within parties also reflects indications of tokenism, where female candidates are often included merely to fulfill administrative requirements without sufficient political support. As a result, women’s representation in the Cilegon DPRD tends to remain at the formal and descriptive levels, while substantive representation remains a challenge in local political practice.